Model Komunikasi Digital Pariwisata Berbasis Integrated Marketing Communicaton dalam Upaya Menciptakan Ketahanan Pangan Masyarakat Desa Watusigar, Yogyakarta - Deni Malik; Maya Sofiana; Mochamad Rizki; Nur Haka Fathurahman; Ryansyah Alfajri (Mandalika Institute, 2026)
Watusigar Village is one of the villages that has adopted the concept of Community-Based Tourism (CBT) as the foundation for developing its tourism attractions. This study aims to analyze the role of an Integrated Marketing Communication (IMC)-based digital tourism communication model in strengthening food security within the Watusigar Village community, Yogyakarta. The research focuses on the utilization of social media as the primary instrument for promoting tourism destinations while simultaneously supporting the local food system. A qualitative approach with a case study design was employed, involving interviews with key stakeholders including tourism village managers, business actors, local food producers, visitors, and local government representatives. Data analysis was conducted using NVivo 14 to identify key themes aligned with the research objectives. The findings indicate that social media, particularly the Instagram account sembrani.watusigar, has proven effective in attracting tourists and building a positive image of Watusigar Village as a tourism destination. Furthermore, the IMC-based digital communication strategy significantly contributes to food security by expanding market access for local food products. These findings affirm that the success of implementing an IMC-based digital tourism communication model relies heavily on strong collaboration among tourism village managers, local government, business actors, and the local community. Such synergy serves as a key factor in achieving sustainable tourism while strengthening food security in Watusigar Village, Yogyakarta.